Inventory and analysis of occupation of parking spaces in public streets in the city of Itabira – MG (Research, Society and Development, 2019)
The inventory and analysis of the occupation and alternation of vehicles (cars and motorcycles) on Itabira’s downtown parking lots can be done by counting and characterizing the existing lanes in that area. The methodology used in this work includes photographic records, notes and a survey with users and merchants in the region. The data was inserted into electronic worksheets to create graphs and make clear the variation of the number of vehicles parked in a time interval of approximately one hour. This report presents the final analysis of the research, proposes improvements for the parking system and provides possible solutions for the parking problems in the region of the banks, in Itabira City.